A study of nanowire junctions and their impact on the properties of nanowire networks - Bellew, Allen T. (Trinity College (Dublin, Ireland). School of Chemistry, 2015)
Nanowire networks are of immense technological interest due to their properties of high transparency, high porosity, flexibility, ease of fabrication, and low cost. Despite the increasing attention these materials continue to receive, there remains a fundamental lack of understanding in the literature regarding the properties of the basic building block of nanowire networks - the nanowire junction. This is highlighted by several recent reports in the literature that attempt to extract the resistance of the junction from bulk measurements, producing inconsistent results. This thesis focuses on addressing this lack of understanding by examining individual junctions composed of both silver and nickel nanowires with passivating surface layers. Passivation layers are ubiquitous throughout nanoscience, and are generally seen as obstacles that must be overcome in order to realise functional devices or applications.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin